A new modular multilevel converter for HVDC applications - Hassan, Zain (2021)
In the coming years, due to an increasing shift towards electric mobility and further industrialisation, a rapid growth in the demand for electricity is expected. At the same time, this energy demand must be met in a clean and sustainable manner, to reduce climate change as well as to ensure security of supply. It is predicted that the High Voltage Direct Current (HVDC) transmission technology will play a key role in the future power systems which are expected to feature higher levels of interconnection and more renewable-based generation. HVDC transmission is preferred over AC transmission in applications such as power transmission over long distances and from offshore wind sources, and interconnection of asynchronous systems. The main elements of an HVDC system are the AC/DC converters that take up the majority of the initial set up cost, and therefore, there has been a huge focus lately on improving these converters in terms of functionality, cost and efficiency.